Impacts of commingling cattle from different sources on their physiological, health, and performance responses during feedlot receiving. Issue 4 (10th November 2020) - Wiegand, Jacob B; Cooke, Reinaldo F; Brandão, Alice P; Schubach, Kelsey M; Colombo, Eduardo A; Daigle, Courtney L; Duff, Glenn C; Gouvêa, Vinicius N
Abstract: This experiment compared physiological, health, and performance responses of beef heifers assigned to different commingling schemes (one, two, or four sources per pen) during a 56-d feedlot receiving period. Ninety-six recently weaned Angus-influenced heifers were obtained from an auction facility. Heifers originated from four cow-calf ranches, and were reared in the same herd within each ranch since birth. Heifers were loaded into two livestock trailers at the auction yard (two sources per trailer; d −2), arranged in two sections of each trailer according to source, and transported for 10 h to stimulate the stress of a long-haul. Heifers were not mixed with cohorts from other sources prior to and at the auction yard. Upon arrival (d −2), shrunk body weight (BW) was recorded and heifers were maintained in four paddocks by source with ad libitum access to a complete starter feed and water for 36 h. On d 0, heifers were ranked by source and shrunk BW and allocated to 1 of 24 drylot pens (four heifers per pen) containing: 1) heifers from a single source (1SRC, n = 8), 2) heifers from two sources (2SRC, n = 8), or 3) heifers from four sources (4SRC, n = 8). From d 0 to d 55, heifers had free-choice access to the complete starter feed and water. Heifers were assessed daily for symptoms of bovine respiratory disease (BRD), and feed intake was recorded from each pen daily. Blood samples were collected on d 0, d 6, d 13, d 27, d 41, and d 55, and shrunk BW (after 16 h of water and feed withdrawal) was recorded on d 56 for average daily gain (ADG). No treatment differences were noted ( P ≥ 0.56) for heifer ADG (mean ± SE = 0.853 ± 0.043 kg/d), final shrunk BW, feed intake, and feed efficiency. No treatment differences were noted ( P ≥ 0.27) for plasma concentrations of cortisol and haptoglobin, and serum concentrations of antibodies against BRD viruses and Mannheimia haemolytica . No treatment differences were noted ( P ≥ 0.17) for incidence of BRD (mean ± SE = 59.3 ± 5.0%) or mortality. The proportion of heifers diagnosed with BRD that required three antimicrobial treatments to regain health increased linearly ( P = 0.03) according to the number of sources (0.0, 12.3, and 20.8% of 1SRC, 2SRC, and 4SRC heifers, respectively; SEM = 7.0). Hence, commingling heifers from different sources did not impact performance, physiological responses, and BRD incidence during a 56-d receiving period, although recurrence of BRD after the second antimicrobial treatment increased according to commingling level.